2009
DOI: 10.1039/b818323f
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new analysis method evaluating adsorption energies for the respective ion-exchanged sites on alkali-metal ion-exchanged ZSM-5 utilizing CO as a probe molecule: IR-spectroscopic and calorimetric studies combined with a DFT method

Abstract: For alkali-metal ion-exchanged ZSM-5 zeolites (MZSM-5; M: Li, Na, K, Rb, Cs) the analysis of ion-exchangeable sites was performed by means of a combined method based on IR spectroscopic and calorimetric measurements using CO as the probe molecule. The heat of adsorption of CO was found to be correlated with an IR frequency of stretching vibration of C-O in the adsorbed species. It was revealed that there exists at least two types of sites capable of ion-exchanging; for the lithium ion-exchanged ZSM-5 (LiZSM-5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Since IR spectra were measured after the evacuation of samples at 25 °C, all three bands are due to CO adsorbed on Cu + cations. Carbonyl complexes formed on cocations (H + , Na + , K + , or Cs + ) are unstable under vacuum at 25 °C; the corresponding adsorption enthalpies are lower than −35 kJ·mol –1 , ,, whereas adsorption enthalpy of the first CO molecule with Cu + is between −110 and −66 kJ·mol –1 . , The IR band at 2155 cm –1 is characteristic for monocarbonyl complexes in high-silica Cu-zeolites. ,, Previous combined experimental and theoretical investigations showed that the stretching frequency of these monocarbonyl species are not site-specific. ,, However, heterogeneity of monocarbonyl species characterized by the IR band at 2155 cm –1 is apparent from TPD and calorimetric measurements on the Cu,Na-FER-8.6–0.31 sample: while the IR spectrum showed only one sharp band at 2155 cm –1 , the TPD and microcalorimetry reveal at least two different adsorption species with interaction energies of 110–105 and 88–85 kJ·mol –1 (Figure B for IR spectra, Figure for the microcalorimetry, and Table for TPD results).…”
Section: Discussionmentioning
confidence: 99%
“…Since IR spectra were measured after the evacuation of samples at 25 °C, all three bands are due to CO adsorbed on Cu + cations. Carbonyl complexes formed on cocations (H + , Na + , K + , or Cs + ) are unstable under vacuum at 25 °C; the corresponding adsorption enthalpies are lower than −35 kJ·mol –1 , ,, whereas adsorption enthalpy of the first CO molecule with Cu + is between −110 and −66 kJ·mol –1 . , The IR band at 2155 cm –1 is characteristic for monocarbonyl complexes in high-silica Cu-zeolites. ,, Previous combined experimental and theoretical investigations showed that the stretching frequency of these monocarbonyl species are not site-specific. ,, However, heterogeneity of monocarbonyl species characterized by the IR band at 2155 cm –1 is apparent from TPD and calorimetric measurements on the Cu,Na-FER-8.6–0.31 sample: while the IR spectrum showed only one sharp band at 2155 cm –1 , the TPD and microcalorimetry reveal at least two different adsorption species with interaction energies of 110–105 and 88–85 kJ·mol –1 (Figure B for IR spectra, Figure for the microcalorimetry, and Table for TPD results).…”
Section: Discussionmentioning
confidence: 99%
“…This value highly concords with the experimental one since the band attributed to the formation of mono-carbonyl, Na + (CO) is located at around 2171 cm À1 , Table 1. Using a small cluster model of Na-ZSM5 zeolite, Kumashiro et al 27 have calculated a similar energy value for the adsorption of a single CO molecule (À22.9 kJ mol À1 ) and have reported n CO stretching frequency at 2180 cm À1 . In contrast, using periodic ferrierite model Nachtigall and co-workers 4 have calculated a slightly higher value of À30 (AE3) kJ mol À1 for the standard adsorption enthalpy of Na + -CO interaction.…”
Section: Dft Study Of Thementioning
confidence: 96%
“…Our characterization methods used CO as a probe molecule that is sensitively adsorbed on the acidic zeometal site. , Figure a shows the CO adsorption isotherm at 298 K for the Ag/MFI sample. A steep rise in the adsorbed CO amount was observed in the low-pressure region; this amount was evaluated to be almost 0.45 mmol g –1 .…”
Section: Resultsmentioning
confidence: 99%